Ultrastructure of cocoa fruits (Theobroma cacao) of cultivars with contrasting susceptibility to Moniliophthora roreri - Flores, Dora (1994)
Moniliasis of cocoa is an important disease caused by the fungus Moniliophthora roreri (Cif & Park) (Evans et al 1978). A study was conducted on the external features of fruits of two cocoa cultivars with different degrees of susceptibility to M. roreri also a comparative study of the exocarp tissues of healthy fruits was conducted. Scanning Electron Microscopy (SEM) and High Resolution Optical Microscopy (HROM) were used respectively. For SEM, sixty-day-old healthy fruits of cvs Pound-7 (susceptible) and UF-296 (moderately resistant) were collected from CATIE's germplasm collection in Turrialba and La Lola, Costa Rica. Apparently, no external anatomic differences between the fruits of the Pound 7 and the UF-296 (moderately resistant) cultivars exist, except for the star-like trichomes in the latter. Both show an alveolar epidemis on which there are noticeable anomocitic-type stomata and a large number of glandular trichomes. For HROM, healthy Pound-7 and UF-296 fruits from La Lola were used, as well as cv. UF-273 resistant to the pathogen. The major histological feature of cv UF-273 and UF-296 was a cellular arrangement of the subepidermic parenchyma which was more compact, probably containing larger amounts of phenolic substances in the vacuoles, as compared to the Pound 7.